KETERKAITAN REVITALISASI KOTA LAMA SEMARANG DENGAN KONDISI SOSIAL EKONOMI MASYARAKAT - Lita Johan Trifena; Santy Paulla Dewi (Jurnal Riptek, 2020)
Revitalization of the Semarang Old City is the government's effort to overcome physical problems as well as promote history tourism as a generator development. Revitalization is focused on physical improvements such as improving infrastructure and facilities, making pedestrians comfortable, and adding street furniture. The physical changes in the area are indicated to have an impact on the socio-economic conditions of the community. Therefore, the purpose of this study is to analyze the relationship between the revitalization and the social and economic conditions of the community. The research method used a quantitative method with a proportional random sampling to 77 respondents. The analysis method used a  linear regression. The results of the analysis show that the revitalization carried out has a positive effect on social conditions and has a negative effect on the economic conditions of the community. This is showed by a decrease in income levels, changes in livelihoods, a decrease in the ability to rent land and inconvenience in living after the revitalization process. On the other hand, revitalization has a positive impact on social aspects, as shown by community interactions. In addition, the area becomes safer after revitalization where the crime rate is getting smaller. The revitalization process should be carried out in a balanced physical and non-physical manner so that the socio-economic conditions of the community are not negatively affected by the revitalizationprocess.